A diet supplemented with hazelnut skin changes the microbial community composition and the biohydrogenation pattern of linoleic acid in the rumen of growing lambs. Issue 1 (1st January 2021) - Daghio, Matteo; Viti, Carlo; Mannelli, Federica; Pauselli, Mariano; Natalello, Antonio; Luciano, Giuseppe; Valenti, Bernardo; Buccioni, Arianna
Abstract: The reuse of by-products from the agro-industry in animal feeding is desirable to increase the sustainability of the productions. Hazelnut skin is a by-product of the food industry and due to the high content in crude fat and phenolic compounds can be potentially used in ruminants' diet. In this study, we characterised and compared the microbial communities of rumen digesta (RD) from lambs fed a diet supplied with hazelnut skin vs. a control diet. Microbial DNA was extracted and high-throughput sequencing of 16S rRNA gene amplicons was performed. Six genera ([ Eubacterium ] nodatum group, Acidaminococcus, Dialister, Erysipelotrichaceae UCG-002, Megasphaera, and Olsenella ) showed a positive correlation with the concentration of C18:1 t 10, and their relative abundance was higher in the RD from lambs fed the control diet, compared to the RD from lambs fed the diet supplied with hazelnut skin. The results suggest that the relative abundance of microorganisms correlated to C18:1 t 10 production in the rumen of animals fed a concentrate-based diet can be reduced by the administration of hazelnut skin. Highlights: A diet with hazelnut skin affected the microbial community in the rumen of lambs The relative abundance of the genus Dialister decreased with hazelnut skin Administration of hazelnut skin can be a strategy to reduce the C18:1 t 10/ t 11 ratio